Integrating Psychosocial Care into Neuro-Oncology: Challenges and Strategies - Chambers, Suzanne K.; Grassi, Luigi; Hyde, Melissa K.; Holland, Jimmie; Dunn, Jeff (Frontiers in Oncology, 2015)
Approximately 256,000 cases of malignant brain and nervous system cancer were diagnosed worldwide during 2012 and 189,000 deaths, with this burden falling more heavily in the developed world. Problematically, research describing the psychosocial needs of people with brain tumours and their carers and the development and evaluation of intervention models has lagged behind that of more common cancers. This may relate, at least in part, to poor survival outcomes and high morbidity associated with this illness; and stigma about this disease. The evidence base for the benefits of psychosocial care in oncology has supported the production of clinical practice guidelines across the globe over the past decade, with a recent mandate to integrate the psychosocial domain and measurement of distress into routine care. Clinical care guidelines for people with brain tumours have emerged, with a building focus on psychosocial and survivorship care. However researchers will need to work intensively with health care providers to ensure future practice is evidence-based and able to be implemented across both acute and community settings and likely within existing resources.